Analytical validation of a flow cytometric protocol for quantification of platelet microparticles in dogs. (30th March 2018) - Cremer, Signe E.; Krogh, Anne K. H.; Hedström, Matilda E. K.; Christiansen, Liselotte B.; Tarnow, Inge; Kristensen, Annemarie T.
Abstract : Background: Platelet microparticles (PMPs) are subcellular procoagulant vesicles released upon platelet activation. In people with clinical diseases, alterations in PMP concentrations have been extensively investigated, but few canine studies exist. Objectives: This study aims to validate a canine flow cytometric protocol for PMP quantification and to assess the influence of calcium on PMP concentrations. Methods: Microparticles (MP) were quantified in citrated whole blood (WB) and platelet‐poor plasma (PPP) using flow cytometry. Anti‐CD61 antibody and Annexin V (AnV) were used to detect platelets and phosphatidylserine, respectively. In 13 healthy dogs, CD61 + /AnV − concentrations were analyzed with/without a calcium buffer. CD61 + /AnV −, CD61 + /AnV +, and CD61 − /AnV + MP quantification were validated in 10 healthy dogs. The coefficient of variation (CV) for duplicate (intra‐assay) and parallel (inter‐assay) analyses and detection limits (DLs) were calculated. Results: CD61 + /AnV − concentrations were higher in calcium buffer; 841, 800 MP/μL (526, 000‐1, 666, 200) vs without; 474, 200 MP/μL (278, 800‐997, 500), P  < .05. In WB, PMP were above DLs and demonstrated acceptable (<20%) intra‐assay and inter‐assay CVs in 9/10 dogs: 1.7% (0.5‐8.9) and 9.0% (0.9‐11.9), respectively, for CD61 + /AnV − and 2.4% (0.2‐8.7) and 7.8% (0.0‐12.8), respectively, for CD61 + /AnV + . Acceptable CVs were not seen for the CD61 − /AnV + MP. In PPP, quantifications were challenged by high inter‐assay CV, overlapping DLs and hemolysis and lipemia interfered with quantification in 5/10 dogs. Conclusions: Calcium induced higher in vitro PMP concentrations, likely due to platelet activation. PMP concentrations were reliably quantified in WB, indicating the potential for clinical applications. PPP analyses were unreliable due to high inter‐CV and DL overlap, and not obtainable due to hemolysis and lipemia interference.